Implementasi Pembelajaran Matematika Berbasis Wirausaha Dalam Menumbuhkan Disposisi Matematis Siswa Sekolah Menengah Kejuruan - Meslita, Rima (Universitas PGRI Madiun, 2023)
The research aims to find ways to implement entrepreneurial-based mathematics learning in cultivating the mathematical dispositions of students at SMKN 1 Tanjung Jabung Barat. This research was analyzed by means of descriptive qualitative. Research subjects employed purposive sampling as many as 10 people. The resultseshowed that in the implementation of learning mathematics in cultivating students' mathematical dispositions, 7 research subjects were included inethe very goodecategory and 3 research subjects were included in the fairly good category. The obstacles encountered in the process of growing the mathematical disposition of students at the School include students not understandingeabout learning simulationsewith the concept of buyingeand selling or better known as Market day. Students think that if an activity involves them spending money or capital, even though the activity is a bridgeefor students to understandethe material. Students with their own understanding without a teacher and learning about these activities makes students unmotivated, which reduces students' creativity and self-confidence